The Power of Exclusion Indigenous People Mapur Bangka - Gilang Setiyo Permadi; Bustami Rahman; Iskandar Zulkarnain (Profesional Muda Cendekia Publishing, 2023)
The closed access to land for the community is an interesting problem to study, because land is a resource that provides benefits for life. The closed access to land is felt by the Mapur Indigenous People who have a constellation of customary forests, the inability to gain access is interpreted as exclusion. Exclusion does not occur randomly, but is shaped by the interaction of power. This research is to analyze the process of exclusion of the Mapur Indigenous People and describe the implications of exclusion for the lives of the Mapur Indigenous People. The case study method is used because of the uniqueness of the cases and their research subjects which are unique and different from other subjects. Collecting data using observation interviews, documentation, and archival records. The results of this study indicate that ini the process of exclusion, it was initiated by the tin case through the deregulation of the tin trading system which made changes to the pattern of life of the Mapur Indigenous People to become modern, with the expansion of oil palm, the Mapur Indigenous People could no longer freely acces tin because land did not exist, also with agriculture. From the process of exclusion, there are forces that work to shape exclusion, namely the market, regulation, coercion, and legitimacy. The implications of this exclusion are loss of land caused by incoming corporations, uprooting of their identity because they feel unappreciated, and conflicts between close relatives or conflicts from within which damage the family structure and interactions between them.